Between Empathy and Privacy: Redefining The Ethical Boundaries of Teachers in The Age of Unlimited Connectivity - Fara Kanza Azzahra; Nadiatus Sarifah; Isna Mazroah; Abdul Azim (Literasi Nusantara, 2026)
The rapid advancement of digital technology has fundamentally transformed the teacher-student relationship, creating an ethical tension between the demand for professional empathy and the protection of teachers' personal privacy. This study aims to analyze the shifting roles and expectations of teachers in the era of unlimited connectivity, examine the ethical dilemmas arising from blurred professional boundaries, and propose a redefinition of ethical boundaries based on digital literacy and contextual policies. Employing a descriptive method and literature review of sources, this research synthesizes theoretical and empirical findings on teacher professionalism, digital ethics, and psychological well-being. The results indicate that unlimited connectivity has shifted teachers' roles from authoritative knowledge transmitters to facilitators and mentors, leading to more horizontal relational dynamics. However, this shift has also intensified ethical dilemmas, including the criminalization of disciplinary actions, the blurring of personal and professional digital identities, and increased psychological stress such as burnout and digital fatigue. The findings further reveal that existing regulations and professional codes of ethics are inadequate to address the complexities of digital communication. The study concludes that redefining ethical boundaries requires a balanced framework integrating enhanced digital literacy for teachers and the development of participatory, context-specific school policies. This redefinition is essential to protect teachers' privacy rights while preserving empathetic, professional educational interactions, thereby ensuring both teacher well-being and the quality of learning in the digital age.